Enalapril in patients after mitral valve replacement - O. L. Barbarash; E. V. Tavlueva; Yu. V. Krotikov; I. N. Sizova; L. S. Barbarash (Кардиоваскулярная терапия и профилактика)
Aim. To assess enalapril effectiveness in myocardial remodeling correction among patients after mitral valve replacement. Material and methods. In total, 54 patients (mean age 46,3±7,6 years) with isolated or prevalent mitral valve stenosis were examined. All participants underwent surgical valve disease correction. In early post-surgery period, all subjects without contraindications started enalapril therapy (2,5-20,0 mg/d). Mean follow-up lasted for 17,1±5,2 months after valve replacement. Clinical and functional status was assessed by NYHA classification and 6-minute walking stress results. Before the surgery and during dynamic follow5up, all patients underwent electrocardiography and echocardiography. Statistical analysis was performed with Statistica 6.0 software (StatSoft, Inc). Results. Assessing post-surgery hemodynamic parameters in atrial fibrillation (AF) patients, the authors observed that enalapril therapy demonstrated more beneficial hemodynamic effects than in sinus rhythm participants. In patients with sinus rhythm, enalapril therapy significantly reduced only pulmonary artery pressure (PAP). Conclusion. Enalapril therapy in patients after mitral valve replacement improves heart chamber size and PAP dynamics, especially in persistent AF participants.